The Influence of Technology-Based Interactive Learning Media on Students' Learning Interest at SD N 35 Bengkulu City - Niarotul Jannah; Nurhayat Lestari Putri . P; Asmara Yumarni; Abdul Aziz (Sekolah Tinggi Agama Islam Al-Furqan, Makassar - Indonesia, 2025)
This research is motivated by the low interest in learning among elementary school students caused by the dominance of conventional learning and the limited use of technology-based learning media. The aim is to determine the effect of technology-based interactive learning media on the interest in learning among fifth-grade students of SDN 35 Bengkulu City. The research method used is a quantitative approach with a quasi-experimental type using a Nonequivalent Control Group Design. The research sample used consisted of two classes, namely the experimental class and the control class with 30 students each. The research instruments were in the form of a learning interest questionnaire and observation sheets. The implications of the research show that interactive learning media can be used as an alternative effective learning strategy to increase student interest in learning in elementary school, as well as encourage teachers to be more active in utilizing technology in the learning process in the digital era. while data analysis uses descriptive statistical tests, normality tests, homogeneity tests, and t-tests (independent sample t-tests). The results of the study indicate that there is an increase in student interest in learning after the use of technology-based interactive learning media. This is evidenced by the increase in the average value from 62 in the pretest to 85 in the posttest, as well as the results of the t test which show that the calculated t value (3.21) is greater than the t table (2.04) with a significance of 0.003 < 0.05. Based on these results, it can be concluded that technology-based interactive learning media has a significant effect on students' learning interest.